Children's Oncology Group Trial AALL1231: A Phase III Clinical Trial Testing Bortezomib in Newly Diagnosed T-Cell Acute Lymphoblastic Leukemia and Lymphoma. Issue 19 (1st July 2022) - Teachey, David T.; Devidas, Meenakshi; Wood, Brent L.; Chen, Zhiguo; Hayashi, Robert J.; Hermiston, Michelle L.; Annett, Robert D.; Archer, J. Hunter; Asselin, Barbara L.; August, Keith J.; Cho, Steve Y.; Dunsmore, Kimberly P.; et al.
Abstract : PURPOSE: To improve the outcomes of patients with T-cell acute lymphoblastic leukemia (T-ALL) and lymphoblastic lymphoma (T-LL), the proteasome inhibitor bortezomib was examined in the Children's Oncology Group phase III clinical trial AALL1231, which also attempted to reduce the use of prophylactic cranial radiation (CRT) in newly diagnosed T-ALL. PATIENTS AND METHODS: Children and young adults with T-ALL/T-LL were randomly assigned to a modified augmented Berlin-Frankfurt-Münster chemotherapy regimen with/without bortezomib during induction and delayed intensification. Multiple modifications were made to the augmented Berlin-Frankfurt-Münster backbone used in the predecessor trial, AALL0434, including using dexamethasone instead of prednisone and adding two extra doses of pegaspargase in an attempt to eliminate CRT in most patients. RESULTS: AALL1231 accrued 824 eligible and evaluable patients from 2014 to 2017. The 4-year event-free survival (EFS) and overall survival (OS) for arm A (no bortezomib) versus arm B (bortezomib) were 80.1% ± 2.3% versus 83.8% ± 2.1% (EFS, P = .131) and 85.7% ± 2.0% versus 88.3% ± 1.8% (OS, P = .085). Patients with T-LL had improved EFS and OS with bortezomib: 4-year EFS (76.5% ± 5.1% v 86.4% ± 4.0%; P = .041); and 4-year OS (78.3% ± 4.9% v 89.5% ± 3.6%; P = .009). No excess toxicity was seen with bortezomib. In AALL0434, 90.8% of patients with T-ALL received CRT. In AALL1231, 9.5% of patients were scheduled to receive CRT. Evaluation of comparable AALL0434 patients who received CRT and AALL1231 patients who did not receive CRT demonstrated no statistical differences in EFS ( P = .412) and OS ( P = .600). CONCLUSION: Patients with T-LL had significantly improved EFS and OS with bortezomib on the AALL1231 backbone. Systemic therapy intensification allowed elimination of CRT in more than 90% of patients with T-ALL without excess relapse. Abstract :